الحذف في ضوء علم لغة النصّ - محمد الأمين مصدق (Université de M'sila, 2019)
في سبعينات القرن الماضي تأسّس فرع معرفي جديد في دوحة اللّسانيات، وجعل من النصّ مدار الدراسة وموضع البحث، ووجّه اهتمامه الرئيس صوب الأدوات والآليات التي تحقّق تماسكه وترابطه. ونحاول في هذا المقال التعرّف على الحذف الذي يعدّ أحد الأدوات النحويّة التي تسهم في اتّساق النصوص، من خلال الوقوف على تعريفه، وأقسامه، ووظيفته في تحقيق تماسك النص، ودور المتلقّي في استخراج المحذوفات وربط شبكة النصّ ببعضها بعض. In the Seventies of the last century a new knowledge branch was established in the Department of Linguistics, it made the text the field of the study and the subject of research. It focused its attention on the tools and mechanisms that achieve its cohesion. In this article we try to identify the Ellipsis, which is one of the grammatical tools that contribute to the consistency of texts, by standing on its concept, its sections, its role in achieving the cohesion of the text, and the role of the recipient in extracting the deleted items and link the text's network to each other.